The impact of social audit in social performance an applied study of the views of a sample of managers and staff of Algerian business organizations - مبروكة, بن الشريف; الشيخ, ساوس (Journal of Economics and Administrative Sciences, 2020)
This research aims at clarifying the concept of social auditing, which is one of the most important reasons for its emergence is social responsibility accounting and its role in measuring the social performance of enterprises. The study also aimed to know how social auditing has an impact and its role in improving the social performance of business organizations, and the research refers to testing the hypotheses of an impact of social auditing on social performance through a commitment to social responsibility. The research sample consisted of 200 individuals from 20 Algerian business organizations and represented individuals who were researched in managers and employees of these organizations, and to achieve research objectives the survey was a tool for collecting information and relying on the partial micro squares method using the PLSPM package in the programming of the R. The results of the field study showed that there is interest on the part of Algerian organizations in social scrutiny by improving its social performance, despite its lack of practice, it is necessary to take care of the subject of social scrutiny by scientific and professional organizations in Algeria by teaching it at the universities and relevant institutes and encouraging research on the subject.